2010
DOI: 10.1016/j.envpol.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drugs in Canadian municipal wastewater and estimates of community drug use

Abstract: Cocaine and amphetamines were detected in untreated and treated sewage in the wastewater treatment plants of three Canadian cities, and community consumption patterns estimated from the concentrations of the drugs in untreated wastewater were consistent with estimates of the use of illicit drugs in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
105
3
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(127 citation statements)
references
References 16 publications
16
105
3
3
Order By: Relevance
“…The amount of these illicit drugs and their precipitated metabolites was relatively low compared to the amount in the dissolved phase (Baker and Kasprzyk-Hordern 2011;Metcalfe et al 2010;Senta et al 2013). Therefore, we only considered the concentrations of dissolved compounds for the estimation of the mass load.…”
Section: Drug Loads In Rivers and The Uncertainty Analysismentioning
confidence: 99%
“…The amount of these illicit drugs and their precipitated metabolites was relatively low compared to the amount in the dissolved phase (Baker and Kasprzyk-Hordern 2011;Metcalfe et al 2010;Senta et al 2013). Therefore, we only considered the concentrations of dissolved compounds for the estimation of the mass load.…”
Section: Drug Loads In Rivers and The Uncertainty Analysismentioning
confidence: 99%
“…Procedural blanks in each matrix were also pre-concentrated to measure SPE recovery of both the DOAs and their surrogates. Automated SPE was carried out using a Gilson GX-271 ASPEC™ instrument using the method described in Metcalfe et al (2010). The eluent was then evaporated to almost dryness using a Savant SPD 131DDA Speed Vac Concentrator connected to a RVT4104 refrigerated vapor trap (Thermo Fisher Scientific, Waltham, MA).…”
Section: Sample Pre-concentrationmentioning
confidence: 99%
“…It is well known however, that the use of psychoactive substances is essentially universal and that they are one of the most recent additions to the list of contaminants of emerging concern in the environment (Boleda et al, 2009;Kasprzyk-Hordern et al, 2010). It is clear from the studies that have identified these compounds in wastewater effluents and surface waters at the nanogram and in some cases, microgram per liter level, that they and many of their main human metabolites, are ubiquitous in the environment (Baker and Kasprzyk-Hordern, 2011;Bartelt-Hunt et al, 2009;Bijlsma et al, 2012Bijlsma et al, , 2013Castiglioni et al, 2006a;Gheorghe et al, 2008;González-Mariño et al, 2011;Hummel et al, 2006;Jones-Lepp et al, 2004;Kasprzyk-Hordern et al, 2009;Metcalfe et al, 2010;Pedrouzo et al, 2011a;Postigo et al, 2011;Zuccato et al, 2005). In fact, these compounds, like many other contaminants of emerging concern have been shown to be resistant to physicochemical and biological treatment at WWTPs and are therefore continuously introduced into the aquatic environment (Boleda et al, 2009;Bolong et al, 2009;Chiaia et al, 2008;Huerta-Fontela et al, 2008;Pal et al, 2013;Postigo et al, 2010;Valcárcel et al, 2012;Yargeau et al, 2013;Zuccato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are often reported not just in terms of the level of compounds detected, but used as an epidemiological measure of drug use including comparisons of drug trends over time and between locations with implications for international drug policy (Metcalfe et al, 2010;van Nuijs et al, 2009). However, without proper data analysis and reporting of analytical results below LOD and LOQ, as well as estimating confidence bounds that incorporate all sources of uncertainty, we believe reporting such comparisons of drug use are premature.…”
Section: Introductionmentioning
confidence: 99%